Youth and the Awakening of Indonesian Literacy from an Islamic Perspective - Saidah Rahmawati; Muthoifin Muthoifin (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2022)
This study aims to reveal the awakening of a good and correct literacy culture or culture of science that is based on Islamic principles, namely the Qur'an, al-Sunnah), friends, and the teachings of Muslim leaders. This research method uses library research or library research which includes systematic identification, analysis of documents containing information related to the research problem. The approach used is a qualitative descriptive type. The results of this study are: 1). Efforts to spread knowledge by looking at the content in the QS. Al-Alaq verses 1-5, 2). take lessons or examples of previous scholars from the success and greatness in studying, 3). Build the quality of the younger generation and institutions of Islamic civilization that are superior and play an important role in the life of the nation and state. So that with the ability to understand a complete literacy culture, and practice it in everyday life, a work will be formed that can contribute to the progress of the Indonesian nation and state.